Characterizing the Performance of Data Management Systems on Hyper-Threaded Architectures - Hassanein, Wessam M.; Hammad, Moustafa A.; Rashid, Layali (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2006: Anais do XVIII International Symposium on Computer Architecture and High Performance Computing, 2006)
As information acquisition and processing applications take greater roles in our everyday life, database management systems are growing in importance. Database management systems have traditionally exhibited poor cache performance and large memory footprints, therefore performing only at a fraction of their ideal execution and exhibiting low processor utilization. Previous research has studied the memory system of database management systems (DBMSs) on research-based simultaneous multithreading (SMT) processors. Several differences have been noted between the real hyper-threaded architecture implemented by the Intel Pentium 4 and the earlier SMT research architectures. Therefore, it is important to study and analyze the performance of modern DBMSs on real SMT processors. This paper characterizes the performance of a prototype open-source DBMS running TPC-C-equivalent benchmark queries on an Intel Pentium 4 hyper-threading processor. We use the performance hardware counters provided by the Pentium 4 to evaluate the micro-architecture and study the memory system behavior of each query running on the data management system. Our results show a performance improvement of up to 1.16 due to hyperthreading